2020
DOI: 10.1167/jov.20.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Attention in visually typical and amblyopic children

Abstract: Amblyopia is a cortical visual disorder caused by unequal visual input to the brain from the two eyes during development. Amblyopes show reduced visual acuity and contrast sensitivity and abnormal binocularity, as well as more "global" perceptual losses, such as figure-ground segregation and global form integration. Currently, there is no consensus on the neural basis for these higher-order perceptual losses. One contributing factor could be that amblyopes have deficiencies in attention, such that the attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…This was observed in the entire sample regardless of the eye tested. That is in line with Sharma et al, (2000), Roberts et al, (2016) and Ramesh et al, (2020), who reported more accurate responses to target Gabor patches on the validly cued side and suggest that both amblyopic observers and neurotypical observers profit from the auditory cue. Interestingly, neural correlates support those findings: ERPs to validly cued standard Gabor patches occurred earlier over contralateral compared to ipsilateral scalp sites in all participants.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This was observed in the entire sample regardless of the eye tested. That is in line with Sharma et al, (2000), Roberts et al, (2016) and Ramesh et al, (2020), who reported more accurate responses to target Gabor patches on the validly cued side and suggest that both amblyopic observers and neurotypical observers profit from the auditory cue. Interestingly, neural correlates support those findings: ERPs to validly cued standard Gabor patches occurred earlier over contralateral compared to ipsilateral scalp sites in all participants.…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, they also found that cueing the attention to the target location in amblyopic observers improved their performance, while cueing attention to an invalid location reduced performance. Indeed, both adults and 5-10 years old children with amblyopia benefit from the cue presentation in a similar manner to neurotypical observers by showing enhanced performance in validly cued trials compared to invalidly cued trials, and reduced performance with invalid cues (Ramesh et al, 2020;Roberts et al, 2016;Sharma et al, 2000), leading to the conclusion that covert spatial selective attention is intact in individuals with amblyopia across different age groups.…”
Section: Introductionmentioning
confidence: 97%
“…Critically, there was a significant 3-way interaction among Session, Diagonal and Group [F(1,12)=5.94, p=.031, η 2 G =.037]: At the trained diagonal, both groups showed higher performance at post-test than pre-test [Neutral group: M=1.83±.13 vs. M=1.10±. 18 (1,6)=21.6, p=.004, η 2 G =.39; both main effect of Diagonal and interaction F<1]. Consistent with these findings, the complementary 2-way (Diagonal X Group) mixed ANOVA of normalized proportion change revealed that only the 2-way interaction between Diagonal (trained, untrained) and Group (Neutral, Attention) was significant [F(1,12)=9.46, p=.010, η 2 G =.13].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, it has been hypothesized that increased fixation instability (particularly for strabismics) leads to higher rates of microsaccades, or fixational eye movements <1°, which results in an amblyopic deficit in selective attention [54]. However, there is controversy as to whether amblyopes reliably generate higher rates of microsaccades (see Discussion of [18]). Further, there is not a direct or causal correspondence between eye movements at any scale and voluntary or involuntary attention (review [71]); neurotypical (review [25]) and amblyopic (e.g.…”
Section: Concomitant Gains In Visual Acuitymentioning
confidence: 99%
See 1 more Smart Citation